Effectiveness of Experiential Learning Based on Multiple Intelligence to Increase MI Student Learning Interest - Moh. Ferdi Hasan; Maemonah Maemonah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
In understanding learning, interest is needed as the main factor, while to foster interest, appropriate and effective learning methods are needed, in which case the multiple intelligence-based experiential learning model is expected to be a solution. The purpose of this study was to determine the effectiveness of multiple intelligence-based experiential learning to increase MI students' learning interest. This research method is quantitative with the type of experimental study, the number of participants is 25 people who are MI students in Kab. Jember, data collection was carried out using a questionnaire technique with pre, experimental and post procedures, while for the analysis test using a paired T-Test. Based on the research conducted, it was found that multiple intelligence-based experiential learning can significantly increase MI students' interest in learning. By carrying out this research, it is expected that MI teachers can apply this learning method so that students' interest in learning increases and results in achievement in the end.